2021
DOI: 10.51248/.v40i4.332
|View full text |Cite
|
Sign up to set email alerts
|

Probable antioxidant therapy of Saffron Crocin in patients with multiple sclerosis: A randomized controlled trial

Abstract: Introduction and Aim: Multiple Multiple sclerosis (MS) is a complex neurological condition  might emerge as a result ofcomplex combination of genetic risk factors with environmental triggers, including oxidative stress. in this study we aimed to evaluate the effects of oral Crocin on oxidative stress in patients with MS.  Materials and Methods: Adjunct to standard treatment, the Crocin group (20 patients) received 30-mg/day (15 mg twice daily) dose of Crocin and placebo group (20 patients) received for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The full-text screening revealed that 18 articles could not be included in the study due to the failure to report the variables (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). In addition, we removed one article because the level of oxidative markers measured were saliva and urine (41). A study that had a short duration of intervention was also excluded from the study (42).…”
Section: Search Resultsmentioning
confidence: 99%
“…The full-text screening revealed that 18 articles could not be included in the study due to the failure to report the variables (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). In addition, we removed one article because the level of oxidative markers measured were saliva and urine (41). A study that had a short duration of intervention was also excluded from the study (42).…”
Section: Search Resultsmentioning
confidence: 99%
“…Ethanoic extract of Saffron enhances antioxidant status in the hippocampus of experimental models of MS (Ghaffari et al 2015). Crocin (30 mg/day) decreases lipid peroxidation and increases total thiol groups and total antioxidant capacity in patients with MS (Ahmadi et al 2020). However, based on the current study we crocin ameliorates adverse effect of the CPZ on antioxidant activity in the brain tissue of the mice, however, we were not able to determine immunohistochemical staining of the brain section to demonstrate demyelination and remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanoic extract of Saffron enhances antioxidant status in the hippocampus of experimental models of MS (Ghaffari et al 2015). Crocin (30 mg/day) decreases lipid peroxidation and increases total thiol groups and total antioxidant capacity in patients with MS (Ahmadi et al 2020). However, based on the current study we crocin ameliorates adverse effect of the CPZ on antioxidant activity in the brain tissue of the mice, however, we were not able to determine immunohistochemical staining of the brain section to demonstrate demyelination and remyelination.…”
Section: Discussionmentioning
confidence: 99%